Molecular neuroanatomy and chemoarchitecture of the neurosecretory preoptic-hypothalamic area in zebrafish larvae - Herget, Ulrich; Wolf, Andrea; Wullimann, Mario F.; Ryu, Soojin (The journal of comparative neurology, 2014)
The paraventricular nucleus (PVN) in mammals is the main hypothalamic nucleus controlling hormone release in the pituitary and plays pivotal roles in homeostasis. While the location of a PVN-homologous region has been described in adult fish as the neurosecretory preoptic area (NPO), this region has not been clearly defined in larval zebrafish due to the difficulty in defining cytoarchitectonic nuclear boundaries in the larval brain. Here we identify the precise location of the larval zebrafish NPO using conserved transcription factor and neuropeptide gene expressions. Our results identify the dorsal half of the preoptic-hypothalamic orthopedia a (otpa) domain as the larval NPO and the homologous region to the mammalian PVN. Further, by reconstructing the locations of cells producing zebrafish neuropeptides found in the mammalian PVN (CCK, CRH, ENK, NTS, SS, VIP, OXT, AVP), we provide the first 3D arrangement map of NPO neuropeptides in the larval zebrafish brain. Our results show striking conservation of transcription factor expression (otp, arx, dlx5a, isl1) in and around the NPO/PVN together with neuropeptide expression within it. Finally, we describe the exact anatomical location of cells producing Oxt and Avp in the adult zebrafish. Thus, our results identify the definitive borders and extent of the PVN homologous region in larval zebrafish and serve as an important basis for cross-species comparisons of PVN/NPO structure and function. J. Comp. Neurol. 522:1542-1564, 2014. © 2013 Wiley Periodicals, Inc.
Gesehen am 15.09.2020
First published: October 11, 2013